A flexible composite thermoelectric film and its preparation method and application
The SnSe precursor and organic polymer are uniformly mixed by electrospinning technology to prepare the obtained flexible composite thermoelectric film. After calcination, the SnSe nanoparticles are uniformly distributed, solving the problem of unstable film performance caused by the aggregation of SnSe nanomaterials, and achieving the preparation of a high-quality and controllable flexible composite thermoelectric film.
Patent Information
- Application Number
- CN202210518245.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-05-13
AI Technical Summary
In the prior art, when preparing SnSe organic composite films, SnSe nanomaterials are prone to aggregation, resulting in poor flexibility, thermoelectric properties and stability of the composite films.
By uniformly mixing the SnSe powder with the organic polymer powder, a mixed liquid is formed as a spinning liquid and electrospinned, a flexible composite thermoelectric film containing SnSe nanoparticles and organic polymer fibers is prepared. After calcination of this method, the SnSe precursor is evenly distributed inside the organic polymer fibers, avoiding the aggregation of material components.
The uniform distribution of SnSe nanoparticles is achieved, the performance stability and thermoelectric properties of flexible composite thermoelectric films are improved, and the problem of unstable film performance in the prior art is solved.
Smart Images

Figure CN115084349B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of thermoelectric materials, and in particular to a flexible composite thermoelectric film and a preparation method and application thereof. Background Art
[0002] Thermoelectric materials can realize direct conversion of heat and electricity, and have very important applications in fields such as waste heat recovery. In recent years, flexible thermoelectric thin film devices have gradually become an emerging development direction in the field of thermoelectrics due to their low cost, bending resistance, strong durability, and great application prospects in the wearable field. As a star material in the field of thermoelectrics, SnSe has become the thermoelectric material with the most practical application potential due to its excellent thermoelectric properties. Research on SnSe thermoelectric materials mainly focuses on the performance of SnSe single crystals or polycrystalline blocks, while research on SnSe thermoelectric films is relatively small. At present, the preparation of SnSe / organic composite films mainly uses liquid phase exfoliation to prepare SnSe nanosheets or nanopowders, which are then mixed with conductive organic matter, and finally the composite film is obtained by spin coating or vacuum filtration. However, the main problems are: (1) the size of the liquid-phase exfoliated SnSe material is uncontrollable and uneven, resulting in unstable performance of the composite material; (2) impurities or Se deficiencies are inevitably introduced during the liquid-phase exfoliation of SnSe materials, which inhibits the intrinsic properties of SnSe and is not conducive to fully exerting the performance of the material; (3) in the process of preparing composite films by spin coating or filtration, due to the difference in quality between SnSe and organic matter, component segregation will occur in the film during the preparation process, and SnSe nanomaterials will aggregate in the composite film, resulting in poor flexibility, thermoelectric properties and stability of the composite film.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a flexible composite thermoelectric film and a preparation method and application thereof, aiming to solve the problem that when the existing method is used to prepare SnSe organic composite films, SnSe nanomaterials will aggregate in the composite film, resulting in poor flexibility, thermoelectric performance and stability of the composite film.
[0005] The technical solution of the present invention is as follows:
[0006] A first aspect of the present invention provides a method for preparing a flexible composite thermoelectric film, comprising the steps of:
[0007] Adding SnSe powder into an organic solvent to obtain a SnSe precursor solution;
[0008] Adding organic polymer powder to the SnSe precursor solution to obtain a mixed solution;
[0009] Using the mixed solution as spinning solution to perform electrostatic spinning to obtain a flexible composite thermoelectric thin film precursor;
[0010] The flexible composite thermoelectric film precursor is calcined to obtain the flexible composite thermoelectric film.
[0011] Optionally, the organic solvent is selected from ethylenedithiol and ethylenediamine.
[0012] Optionally, in the mixed solution, the mass ratio of the SnSe powder to the organic polymer powder is 1:(1-50).
[0013] Optionally, the organic polymer is selected from at least one of polyvinyl pyrrolidone, polyaniline and polyvinyl alcohol.
[0014] Optionally, the process parameters of the electrospinning are as follows:
[0015] The mixed solution delivery speed is 10 to 200 μL / min, and the spinning voltage is 5 to 30 kV.
[0016] Optionally, the electrospinning process using the mixed solution as spinning solution further includes a drying step.
[0017] Optionally, the step of calcining the flexible composite thermoelectric thin film precursor specifically includes:
[0018] The flexible composite thermoelectric film precursor is placed in a vacuum tube furnace and calcined under argon protection.
[0019] Optionally, the calcination temperature is 200 to 500° C., and the calcination time is 1 to 30 minutes.
[0020] A second aspect of the present invention provides a flexible composite thermoelectric film, wherein the flexible composite thermoelectric film is prepared by the preparation method of the present invention as described above.
[0021] The third aspect of the present invention provides an application of the flexible composite thermoelectric film as described above in a thermoelectric device.
[0022] Beneficial effects: The present invention fully mixes the SnSe precursor solution and the organic polymer to form a mixed solution, uses the mixed solution as the spinning solution, and uses the electrospinning technology to prepare a flexible composite thermoelectric film containing SnSe nanoparticles and organic polymer fibers. In the process of preparing the spinning solution, the SnSe precursor and the organic polymer are evenly mixed in the organic solvent, and there is no problem of aggregation of material components; in the electrospinning process, after the solvent evaporates, a flexible composite thermoelectric film precursor including the SnSe precursor and the organic polymer fiber is obtained, and the SnSe precursor is evenly distributed inside the organic polymer fiber obtained by electrospinning, and the presence of the organic polymer fiber is conducive to isolating or slowing down the contact between the SnSe precursor and the air, and protecting the SnSe precursor from being stably present; after calcination, the SnSe precursor evenly distributed inside the organic polymer fiber is in situ converted into SnSe nanoparticles, that is, after calcination, the SnSe particles can be evenly distributed inside the organic polymer fiber without aggregation, and a flexible composite thermoelectric film is obtained. The method provided by the present invention can effectively control the size and thickness of the film, and can simply and efficiently realize the high-quality controllable preparation of the flexible composite thermoelectric film, thereby solving the problem that when the existing method is used to prepare the SnSe organic composite film, SnSe nanomaterials will aggregate in the composite film, resulting in poor flexibility, thermoelectric performance and stability of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the preparation process of the flexible composite thermoelectric film in an embodiment of the present invention.
[0024] Figure 2 This is the XRD diagram of the flexible composite thermoelectric film prepared in Example 1 of the present invention.
[0025] Figure 3a is a SEM image of the flexible composite thermoelectric film prepared in Example 2 of the present invention, Figure 3b This is another SEM image of the flexible composite thermoelectric film prepared in Example 2 of the present invention.
[0026] Figure 4 (a) is a physical picture of the flexible composite thermoelectric film prepared in Example 3 of the present invention, and (b) is a SEM picture of the flexible composite thermoelectric film prepared in Example 3 of the present invention.
[0027] Figure 5 This is a graph showing the change in thermoelectric properties of the flexible composite thermoelectric film prepared in Example 4 of the present invention as a function of different calcination temperatures.
[0028] Figure 6 This is a graph showing the change in thermoelectric performance of the flexible composite thermoelectric film prepared in Example 5 of the present invention as a function of calcination time. DETAILED DESCRIPTION
[0029] The present invention provides a flexible composite thermoelectric film and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0031] The present invention provides a method for preparing a flexible composite thermoelectric film. Figure 1 As shown, wherein the steps include:
[0032] S1, adding SnSe powder into an organic solvent to obtain a SnSe precursor solution;
[0033] S2, adding organic polymer powder to the SnSe precursor solution to obtain a mixed solution;
[0034] S3, using the mixed solution as a spinning solution to perform electrospinning to obtain a flexible composite thermoelectric thin film precursor;
[0035] S4. calcining the flexible composite thermoelectric thin film precursor to obtain the flexible composite thermoelectric thin film.
[0036] In the embodiment of the present invention, the SnSe precursor solution and the organic polymer are fully mixed to form a mixed solution, and the mixed solution is used as the spinning solution, and the flexible composite thermoelectric film containing SnSe nanoparticles and organic polymer fibers is prepared by electrospinning technology, wherein the organic polymer fibers constitute a flexible film in the form of non-woven fabrics, and the SnSe nanoparticles are distributed inside and on the surface of the organic polymer fibers. In the preparation process of the spinning solution, the SnSe precursor and the organic polymer are uniformly mixed in the organic solvent, and there is no problem of aggregation of material components; in the electrospinning process, after the solvent evaporates, a flexible composite thermoelectric film precursor including the SnSe precursor and the organic polymer fiber is obtained, and the SnSe precursor is uniformly distributed inside the organic polymer fiber obtained by electrospinning, and the presence of the organic polymer fiber is conducive to isolating or slowing down the contact between the SnSe precursor and the air, and protecting the SnSe precursor from being stably present; after calcination, the SnSe precursor uniformly distributed inside the organic polymer fiber is in situ converted into SnSe nanoparticles, that is, after calcination, the SnSe particles can be uniformly distributed inside the organic polymer fiber without aggregation, and a flexible composite thermoelectric film is obtained. During the calcination process, due to the difference in thermal expansion coefficients between organic polymer fibers and SnSe particles and the deformation process of the SnSe precursor being converted into SnSe particles, a small portion of the SnSe precursor inside the organic polymer fiber but close to the surface of the organic polymer fiber will be converted into SnSe particles while being evenly distributed on the surface of the organic polymer fiber without aggregation, thereby making the surface of the organic polymer fiber slightly rougher than before calcination. The method provided by the present invention can effectively control the size and thickness of the film, and can simply and efficiently achieve high-quality controllable preparation of flexible composite thermoelectric films, solving the problem that SnSe nanomaterials will aggregate in the composite film when preparing SnSe organic composite films in the existing method, resulting in poor flexibility, thermoelectric performance and stability of the composite film. At the same time, the size of the liquid-phase stripped SnSe material in the prior art is uncontrollable and uneven in size, resulting in unstable performance of the composite film; impurities will inevitably be introduced or Se will be missing during the liquid-phase stripping of the SnSe material, which will inhibit the intrinsic performance of SnSe and is not conducive to fully exerting the performance of the material. Compared with the preparation method of the composite film in the prior art, the SnSe nanoparticles in the flexible composite thermoelectric film prepared by the method provided by the present invention are of controllable size and uniform size, and the introduction of impurities can be avoided during the preparation process, so that the performance of the prepared flexible composite thermoelectric film is stable.
[0037] The flexible composite thermoelectric film provided by the embodiment of the present invention comprises organic polymer fibers and SnSe nanoparticles distributed inside the organic polymer fibers and on the surface of the organic polymer. The organic polymer fibers can improve the flexibility of the flexible composite thermoelectric film, and the lower thermal conductivity of the organic polymer fibers helps to maintain a higher temperature difference between the two ends of the flexible composite thermoelectric film, thereby improving the thermoelectric performance of the flexible composite thermoelectric film; the SnSe nanoparticles are used as thermoelectric sensitive materials to achieve thermoelectric conversion.
[0038] In step S1, before adding the SnSe powder to the organic solvent, the SnSe powder can be ground according to actual needs to reduce the particle size. In specific implementation, an appropriate amount of ethylenediamine can be added during the grinding process to make the particle size more uniform. Then, the ground SnSe powder is added to the organic solvent and fully stirred at room temperature to obtain a uniform SnSe precursor solution.
[0039] In one embodiment, the organic solvent is selected from ethylenedithiol and ethylenediamine. The use of this organic solvent can fully dissolve the SnSe powder to form a SnSe precursor solution, which is more suitable for subsequent electrospinning.
[0040] In a specific embodiment, the organic solvent is selected from ethylenedithiol and ethylenediamine. For example, the volume ratio of ethylenedithiol to ethylenediamine is 1:4.
[0041] In step S2, the organic polymer powder is slowly added to the SnSe precursor solution at room temperature and under continuous stirring until the organic polymer powder is completely dissolved to obtain a uniform mixed solution. The uniform mixed solution is used for electrospinning to avoid aggregation of material components.
[0042] In one embodiment, in the mixed solution, the mass ratio of the SnSe powder to the organic polymer powder is 1:(1-50). Under this ratio, the prepared flexible composite thermoelectric film has excellent thermoelectric performance and flexibility, so that it can have excellent thermoelectric performance and bend-resistant.
[0043] In one embodiment, the organic polymer is selected from at least one of polyvinyl pyrrolidone, polyaniline, and polyvinyl alcohol, but is not limited thereto. These organic substances can enable electrospinning to proceed smoothly and ensure that the prepared flexible composite thermoelectric film has sufficient flexibility and conductivity.
[0044] In step S3, in one embodiment, the electrospinning process parameters are as follows:
[0045] The mixed solution delivery speed is 10 to 200 μL / min, and the spinning voltage is 5 to 30 kV.
[0046] In a specific implementation, the mixed solution is loaded into a syringe and delivered at a speed of 10 to 200 μL / min at a voltage of 5 to 30 kV.
[0047] In one embodiment, the electrospinning process using the mixed solution as the spinning solution further includes a drying step. Specifically, the electrospinning process using the mixed solution as the spinning solution is performed, and the flexible composite thermoelectric thin film precursor is obtained after drying.
[0048] In step S4, in one embodiment, the step of calcining the flexible composite thermoelectric thin film precursor specifically includes:
[0049] The flexible composite thermoelectric film precursor is placed in a vacuum tube furnace and calcined under argon protection.
[0050] After the flexible composite thermoelectric thin film precursor is calcined, the SnSe precursor therein is in-situ transformed into SnSe nanoparticles, which are evenly distributed inside and on the surface of the organic polymer fiber without aggregation.
[0051] In one embodiment, the calcination temperature is 200-500°C, and the calcination time is 1-30 min. For example, the calcination temperature can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, and the calcination time can be 1 min, 2 min, 5 min, 8 min, 10 min, 15 min, 20 min, 25 min or 30 min, etc.
[0052] The embodiment of the present invention also provides a flexible composite thermoelectric film, wherein the flexible composite thermoelectric film is prepared by the preparation method described above in the embodiment of the present invention, and the flexible composite thermoelectric film includes organic polymer fibers and SnSe nanoparticles uniformly distributed inside and on the surface of the organic polymer fibers. The organic polymer fibers can improve the flexibility of the flexible composite thermoelectric film, and the lower thermal conductivity of the organic polymer fibers helps to maintain a higher temperature difference at both ends of the flexible composite thermoelectric film, thereby improving the thermoelectric performance of the flexible composite thermoelectric film; the SnSe nanoparticles are used as thermoelectric sensitive materials to achieve thermoelectric conversion.
[0053] The embodiment of the present invention also provides an application of the flexible composite thermoelectric film as described above in the embodiment of the present invention in a thermoelectric device. The flexible composite thermoelectric film provided by the embodiment of the present invention has good thermoelectric performance and can be used in thermoelectric devices. Specifically, the flexible composite thermoelectric film provided by the embodiment of the present invention can be cut to form a flexible thermoelectric device, which is further applied to the wearable field.
[0054] The following describes it in detail through specific embodiments.
[0055] Example 1
[0056] Weigh 200 mg of SnSe powder and grind it for 30 min to reduce the particle size. Add 1 mL of ethylenediamine during the grinding process. Add the ground SnSe powder into a mixed solution of 10 mL of ethylenedithiol and ethylenediamine (wherein the volume of ethylenedithiol is 2 mL), stir it for 1 h at room temperature to obtain a uniform SnSe precursor solution.
[0057] Slowly add 4 g of polyvinyl alcohol to the above SnSe precursor solution and continue stirring at room temperature until the polyvinyl alcohol is completely dissolved to obtain a uniform mixed solution;
[0058] The mixed solution was loaded into a syringe, the mixed solution delivery speed was 10 μL / min, the output voltage of the high-voltage power supply was 5 KV, and electrospinning was performed to form a film, and then dried in a vacuum drying oven at 50° C. for 20 min to obtain a flexible composite thermoelectric film precursor;
[0059] The flexible composite thermoelectric film precursor was placed in a vacuum tube furnace and calcined at 300° C. for 10 min under argon protection to obtain a flexible composite thermoelectric film.
[0060] Figure 2 This is the XRD diagram of the flexible composite thermoelectric film prepared in Example 1.
[0061] Example 2
[0062] Weigh 200 mg of SnSe powder and grind it for 30 min to reduce the particle size. Add 1 mL of ethylenediamine during the grinding process. Add the ground SnSe powder into a mixed solution of 10 mL of ethylenedithiol and ethylenediamine (wherein the volume of ethylenedithiol is 2 mL), stir it for 1 h at room temperature to obtain a uniform SnSe precursor solution.
[0063] Slowly add 4.5 g of polyvinyl pyrrolidone to the above SnSe precursor solution, and continue stirring at room temperature until the polyvinyl pyrrolidone is completely dissolved to obtain a uniform mixed solution;
[0064] The mixed solution was loaded into a syringe, the mixed solution delivery speed was 30 μL / min, the output voltage of the high-voltage power supply was 10 KV, and electrospinning was performed to form a film, and then dried in a vacuum drying oven at 50° C. for 20 min to obtain a flexible composite thermoelectric film precursor;
[0065] The flexible composite thermoelectric film precursor was placed in a vacuum tube furnace and calcined at 400° C. for 5 minutes under argon protection to obtain a flexible composite thermoelectric film.
[0066] Figure 3a and 3b is a SEM image of the flexible composite thermoelectric film prepared in Example 2. Figure 3b It can be seen that the SnSe nanoparticles are evenly distributed on the surface of the organic polymer fibers.
[0067] Example 3
[0068] Weigh 200 mg of SnSe powder and grind it for 30 min to reduce the particle size. Add 1 mL of ethylenediamine during the grinding process. Add the ground SnSe powder into a mixed solution of 10 mL of ethylenedithiol and ethylenediamine (wherein the volume of ethylenedithiol is 2 mL), stir it for 1 h at room temperature to obtain a uniform SnSe precursor solution.
[0069] Slowly add 5 g of polyvinyl pyrrolidone to the above SnSe precursor solution and continue stirring at room temperature until the polyvinyl pyrrolidone is completely dissolved to obtain a uniform mixed solution;
[0070] The mixed solution was loaded into a syringe, the mixed solution delivery speed was 50 μL / min, the output voltage of the high-voltage power supply was 15 KV, and electrospinning was performed to form a film, and then dried in a vacuum drying oven at 50° C. for 20 min to obtain a flexible composite thermoelectric film precursor;
[0071] The flexible composite thermoelectric film precursor was placed in a vacuum tube furnace and calcined at 400° C. for 10 min under argon protection to obtain a flexible composite thermoelectric film.
[0072] Figure 4 (a) is a physical picture of the flexible composite thermoelectric film prepared in Example 3. Figure 4 (b) SEM image of the flexible composite thermoelectric film prepared in Example 3.
[0073] Example 4
[0074] Weigh 200 mg of SnSe powder and grind it for 30 min to reduce the particle size. Add 1 mL of ethylenediamine during the grinding process. Add the ground SnSe powder into a mixed solution of 10 mL of ethylenedithiol and ethylenediamine (wherein the volume of ethylenedithiol is 2 mL), stir it for 1 h at room temperature to obtain a uniform SnSe precursor solution.
[0075] Slowly add 1 g of polyaniline to the above SnSe precursor solution and continue stirring at room temperature until the polyaniline is completely dissolved to obtain a uniform mixed solution;
[0076] The mixed solution was loaded into a syringe, the mixed solution delivery speed was 20 μL / min, the output voltage of the high-voltage power supply was 12 KV, and electrospinning was performed to form a film, and then dried in a vacuum drying oven at 50° C. for 20 min to obtain a flexible composite thermoelectric film precursor;
[0077] The flexible composite thermoelectric film precursor was placed in a vacuum tube furnace, and calcined at 200° C., 250° C., 300° C., 350° C., 400° C., 450° C., and 500° C. for 10 min, respectively, under argon protection to obtain a flexible composite thermoelectric film.
[0078] Figure 5 The figure shows the change of thermoelectric performance of the flexible composite thermoelectric film prepared in Example 4 with different calcination temperatures. Under the condition of calcination time of 10 min, as the calcination temperature increases, the power factor of the flexible composite thermoelectric film increases first and then decreases. When the calcination temperature is 400°C, the power factor of the flexible composite thermoelectric film is the largest.
[0079] Example 5
[0080] Weigh 200 mg of SnSe powder and grind it for 30 min to reduce the particle size. Add 1 mL of ethylenediamine during the grinding process. Add the ground SnSe powder into a mixed solution of 10 mL of ethylenedithiol and ethylenediamine (wherein the volume of ethylenedithiol is 2 mL), stir it for 1 h at room temperature to obtain a uniform SnSe precursor solution.
[0081] Slowly add 0.5 g of polyaniline to the above SnSe precursor solution and continue stirring at room temperature until the polyaniline is completely dissolved to obtain a uniform mixed solution;
[0082] The mixed solution was loaded into a syringe, the mixed solution delivery speed was 50 μL / min, the output voltage of the high-voltage power supply was 10 KV, and electrospinning was performed to form a film, and then dried in a vacuum drying oven at 50° C. for 20 min to obtain a flexible composite thermoelectric film precursor;
[0083] The flexible composite thermoelectric thin film precursor was placed in a vacuum tube furnace, and calcined at 400° C. for 1 min, 3 min, 5 min, 10 min, 15 min, 20 min, and 30 min, respectively, under argon protection to obtain a flexible composite thermoelectric thin film.
[0084] Figure 6 This is a graph showing how the thermoelectric properties of the flexible composite thermoelectric film prepared in Example 5 change with calcination time. Under the condition of a calcination temperature of 400°C, with increasing calcination time, the power factor of the flexible composite thermoelectric film shows a trend of first increasing and then decreasing. When the calcination time is 10 min, the power factor of the flexible composite thermoelectric film is the largest.
[0085] In summary, the present invention provides a flexible composite thermoelectric film and a preparation method and application thereof. The present invention fully mixes a SnSe precursor solution and an organic polymer to form a mixed solution, and uses the mixed solution as a spinning solution to prepare a flexible composite thermoelectric film containing SnSe nanoparticles and organic polymer fibers by using an electrospinning technology, wherein the organic polymer fibers constitute a flexible film in the form of a non-woven fabric, and the SnSe nanoparticles are distributed inside and on the surface of the organic polymer fibers. In the process of preparing the spinning solution, the SnSe precursor and the organic polymer are uniformly mixed in the organic solvent, and there is no problem of aggregation of material components; in the electrospinning process, after the solvent evaporates, a flexible composite thermoelectric film precursor formed by the SnSe precursor and the organic polymer fiber is obtained, and the SnSe precursor is uniformly distributed inside the organic polymer fiber obtained by electrospinning, and the presence of the organic polymer fiber is conducive to isolating or slowing down the contact between the SnSe precursor and the air, and protecting the SnSe precursor from being stably present; after calcination, the SnSe precursor uniformly distributed inside the organic polymer fiber is in situ converted into SnSe nanoparticles, that is, after calcination, the SnSe particles can be uniformly distributed inside the organic polymer fiber without aggregation, and a flexible composite thermoelectric film is obtained. During the calcination process, due to the difference in thermal expansion coefficients between the organic polymer fiber and the SnSe particles and the deformation process of the SnSe precursor being converted into SnSe particles, a small portion of the SnSe precursor inside the organic polymer fiber but close to the surface of the organic polymer fiber will be converted into SnSe particles and uniformly distributed on the surface of the organic polymer fiber without aggregation. The method provided by the present invention can effectively control the size and thickness of the film, and can simply and efficiently realize the high-quality controllable preparation of the flexible composite thermoelectric film, thereby solving the problem that when the existing method is used to prepare the SnSe organic composite film, SnSe nanomaterials will aggregate in the composite film, resulting in poor flexibility, thermoelectric performance and stability of the composite film.
[0086] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a flexible composite thermoelectric film, characterized in that: Includes steps: Adding SnSe powder into an organic solvent to obtain a SnSe precursor solution; Adding organic polymer powder to the SnSe precursor solution to obtain a mixed solution; Using the mixed solution as spinning solution to perform electrostatic spinning to obtain a flexible composite thermoelectric thin film precursor; The flexible composite thermoelectric film precursor is calcined to obtain the flexible composite thermoelectric film; The organic solvent is selected from ethylenedithiol and ethylenediamine; In the mixed solution, the mass ratio of the SnSe powder to the organic polymer powder is 1:(1-50); The process parameters of the electrospinning are as follows: The mixed solution delivery rate is 10~200μL / min, and the spinning voltage is 5~30kV; The calcination temperature is 200-500°C and the calcination time is 1-30min; The flexible composite thermoelectric film comprises organic polymer fibers and SnSe nanoparticles distributed inside and on the surface of the organic polymer fibers.
2. The method for preparing the flexible composite thermoelectric film according to claim 1, characterized in that: The organic polymer powder is selected from at least one of polyvinyl pyrrolidone, polyaniline and polyvinyl alcohol.
3. The method for preparing the flexible composite thermoelectric film according to claim 1, characterized in that: The method further comprises a drying step after the electrostatic spinning using the mixed solution as the spinning solution.
4. The method for preparing a flexible composite thermoelectric film according to claim 1, characterized in that: The step of calcining the flexible composite thermoelectric thin film precursor specifically includes: The flexible composite thermoelectric film precursor is placed in a vacuum tube furnace and calcined under argon protection.
5. A flexible composite thermoelectric film, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the flexible composite thermoelectric film as claimed in claim 5 in a thermoelectric device.
Citation Information
Patent Citations
Organic-inorganic hybrid nanofiber for thermoelectric application and method of forming the same
US20110129668A1